2018
DOI: 10.1029/2018jc013852
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Semidiurnal Internal Tides in the Andaman Sea

Abstract: A detailed energetic estimate of the barotropic and baroclinic semidiurnal internal tides over the Andaman Sea is performed by using the three-dimensional Massachusetts Institute of Technology general circulation model. Model-simulated currents and density fields are validated using in situ observations with high temporal resolution from a buoy located at 10.5°N, 94°E. The generation and dissipation regions of internal tides and their propagation in the domain are identified by quantifying the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
5
19
0
Order By: Relevance
“…Along the AN Ridge, large M 2 energy conversion occurs in the southern (1–4 W/m 2 in Box IV) and northern parts (0.1–1.4 W/m 2 in Box III). Strong internal tide generation along the AN Ridge was reported by Mohanty et al () also.…”
Section: Resultssupporting
confidence: 52%
“…Along the AN Ridge, large M 2 energy conversion occurs in the southern (1–4 W/m 2 in Box IV) and northern parts (0.1–1.4 W/m 2 in Box III). Strong internal tide generation along the AN Ridge was reported by Mohanty et al () also.…”
Section: Resultssupporting
confidence: 52%
“…The value of the bottom drag coefficient is kept constant at 0.0025 in this configuration. The 3D model set-up is similar to Mohanty et al 13 , which is used to study the energetics of internal tides in the Andaman Sea, except that the western boundary is extended to include RAMA buoy location. The same model is also used in several studies 14 16 for understanding the IWs in the western Bay of Bengal.…”
Section: Methodsmentioning
confidence: 99%
“…(7). In addition, Mohanty et al 13 reported that tendency and advection terms are small compared to other terms along the AN Islands and Andaman Sea. Barotropic M 2 tide loses about 65 GW of tidal energy in the entire model domain, in which about 28.5% (19 GW) of this energy is lost by internal tide dissipation and rest of the energy is dissipated by means of bottom friction.…”
Section: Model Simulationsmentioning
confidence: 99%